2020
DOI: 10.1038/s41598-020-71470-4
|View full text |Cite
|
Sign up to set email alerts
|

Metformin decreases bacterial trimethylamine production and trimethylamine N-oxide levels in db/db mice

Abstract: The current study aimed to explore whether metformin, the most widely prescribed oral medication for the treatment of type 2 diabetes, alters plasma levels of cardiometabolic disease-related metabolite trimethylamine N-oxide (TMAO) in db/db mice with type 2 diabetes. TMAO plasma concentration was up to 13.2-fold higher in db/db mice when compared to control mice, while in db/db mice fed choline-enriched diet, that mimics meat and dairy product intake, TMAO plasma level was increased 16.8-times. Metformin (250 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Consistent with the study of Li, JV et al, our results suggested that PAGln was signi cantly correlated with Klebsiella [52]. Klebsiella is widely believed to be a pathogenic bacterium and a strain with the TMA gene [53][54][55]. TMA is an essential precursor of the gut microbiota metabolite TMAO, which has been found to promote thrombosis via increasing platelet reactivity [56].…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with the study of Li, JV et al, our results suggested that PAGln was signi cantly correlated with Klebsiella [52]. Klebsiella is widely believed to be a pathogenic bacterium and a strain with the TMA gene [53][54][55]. TMA is an essential precursor of the gut microbiota metabolite TMAO, which has been found to promote thrombosis via increasing platelet reactivity [56].…”
Section: Discussionsupporting
confidence: 89%
“…Metformin stimulates the activity of endocrine cells by regulating bile acid conversion, improving intestinal permeability, reducing endotoxin levels, and enhancing the release of GLP-1 and PYY peptides ( 126 ). Metformin also decreases the TMA level and the growth of bacteria that produce it in the gut, and thus the circulating TMAO level in mice ( 127 ). The fact that transferring the microbiota from metformin-treated mice improves metabolic traits in aged mice indicates that the shifts in the gut microbiota by metformin treatment are beneficial ( 111 ).…”
Section: Therapeutic Potential Of Gut Microbiota For T2dmentioning
confidence: 99%
“…As the production of TMA is strictly microbiota-dependent, another limitation is that we were not able to collect samples to assess the impact of FMD on gut microbiota. Some studies state that alterations in microbiota composition that favour TMA-producing bacteria are a possible mechanism by which plasma TMAO levels increase in T2D patients [ 54 , 55 ]. However, recent research shows that some of the typical deviations observed in gut microbiota composition in patients with T2D [ 56 , 57 ] or atherosclerosis [ 58 ] can be restored by FMD [ 59 , 60 ], thus possibly lowering TMA production and reducing CVD risks.…”
Section: Discussionmentioning
confidence: 99%